A case of acute gastric volvulus due to diaphragmatic hernia in an adult with kyphoscoliosis - Meshram, Namvir; Gadhire, Minakshi; Kumar, Vineet (International Surgery Journal, 2019)
Acute gastric volvulus on diaphragmatic hernia is a rare and life-threatening condition, which is seen mostly in fifth decade of life. Presented with vague symptoms of abdominal pain mostly epigastric in nature, retching, may or may not be associated with vomiting, hematemesis, sometime difficult to pass nasogastric tube (Borchardt triad’s). Hereby we report a case of 48 year old male with known case of kyphoscoliosis who came with hematemesis and vomiting only; on investigation chest with abdomen X ray, USG, upper GI scopy and CT chest with abdomen, suggestive of gastric volvulus with diaphragmatic hernia and kyphoscoliosis. Patient was operated; as in acute gastric volvulus delay may result in complication like perforation and gangrene which can lead to increase morbidity and mortality in this patient; derotation of stomach done and diaphragmatic defect repaired with meshplasty, gastropexy with gastrostomy done. Postoperative course was uneventful.